PENYULUHAN ANTI KORUPSI LINTAS KALANGAN PADA MASYARAKAT DESA JEMARAS KABUPATEN KOTAWARINGIN TIMUR - Ahmad, Sabarudin; Maulana, Achmad; Jayanti, Irma; Safrudin, Safrudin; Rahman, Alief Aulia; Purwanti, Fitri (HIKMAYO: JURNAL PENGABDIAN MASYARAKAT AMAYO, 2023)
The most cases of acting against corruption by law enforcement officers (APH) occurred in the village budget sector, namely 154 cases in 2021 with potential state losses of IDR 233 billion. To prevent criminal acts of corruption at the village level, the author provides community service by conducting anti-corruption outreach, especially in Jemaras village, Cempaga district, East Kotawaringin regency. The method used was Asset Based Communities Development (ABCD), by tracing the assets in Jemaras village, it was then discovered that Jemaras village was a candidate for anti-corruption village in the East Kotawaringin regency. The results of this service show that people who gain an understanding of the dangers of corruption and the importance of preventing it become concerned about the village they live in all this time. The target of the activities aimed at various groups, starting from village officials, the general public, and children, aims to ensure that all parties can participate in making Jemaras village an anti-corruption village in the East Kotawaringin regency.